Asxl1 exerts an antiproliferative effect on mouse lung maturation via epigenetic repression of the E2f1-Nmyc axis. Issue 11 (November 2018) - Moon, Seungtae; Im, Sun-Kyoung; Kim, Nackhyoung; Youn, Hyesook; Park, Ui-Hyun; Kim, Joo-Yeon; Kim, A.-Reum; An, So-Jung; Kim, Ji-Hoon; Sun, Woong; Hwang, Jin-Taek; Kim, Eun-Joo; et al.
Abstract Although additional sex combs-like 1 (ASXL1) has been extensively described in hematologic malignancies, little is known about the molecular role of ASXL1 in organ development. Here, we show thatAsxl1 ablation in mice results in postnatal lethality due to cyanosis, a respiratory failure. This lung defect is likely caused by higher proliferative potential and reduced expression of surfactant proteins, leading to reduced air space and defective lung maturation. By microarray analysis, we identified E2F1-responsive genes, includingNmyc, as targets repressed by Asxl1.Nmyc andAsxl1 are reciprocally expressed during the fetal development of normal mouse lungs, whereasNmyc downregulation is impaired inAsxl1 -deficient lungs. Together with E2F1 and ASXL1, host cell factor 1 (HCF-1), purified as an Asxl1-bound protein, is recruited to the E2F1-binding site of theNmyc promoter. The interaction occurs between the C-terminal region of Asxl1 and the N-terminal Kelch domain of HCF-1. Trimethylation (me3) of histone H3 lysine 27 (H3K27) is enriched in theNmyc promoter uponAsxl1 overexpression, whereas it is downregulated inAsxl1 -deleted lung and -depleted A549 cells, similar to H3K9me3, another repressive histone marker. Overall, these findings suggest that Asxl1 modulates proliferation of lung epithelial cells via the epigenetic repression of Nmyc expression, deficiency of which may cause hyperplasia, leading to dyspnea.